Do preferences for urban amenities really differ by skill? - Melanie Arntz; Eduard Brüll; Cäcilia Lipowski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
City-level policies often aim at attracting skilled workers by improving urban amenities. However, due to endogeneity problems, studies relying on revealed preferences have difficulties in providing evidence for the basic premise that skilled workers place a higher value on urban amenities than less skilled individuals. Therefore, we use a stated- preference experiment to directly examine preferences for urban amenities. In a custom survey, we elicit hypothetical job choices between two cities that differ in wages and a set of urban amenities. We find that amenities are important determinants of city choice, with respondents willing to forgo a significant fraction of their wage to live in a city with better amenities. Most strikingly, we do not find any preference heterogeneity between workers differing by education or creative class membership. Instead, we uncover large heterogeneities mainly along family-related mobility constraints and unobserved dimensions. Our results imply that there is not much scope for amenity-oriented policies to improve the local skill mix. Rather, the urban skill bias reflects the incapability of less skilled individuals to afford living in and moving to their preferred places, resulting in significant welfare losses.
Keywords: R12; R22; R58; 330; Urban amenities; regional policy; internal migration; skill selective migration